A new insight into meat toughness of callipyge lamb loins - The relevance of anti-apoptotic systems to decreased proteolysis. (June 2018) - Cramer, Traci; Penick, Moriah L.; Waddell, Jolena N.; Bidwell, Chris A.; Kim, Yuan H. Brad
Abstract: The objective of this study was to determine associations of small heat shock proteins (sHSPs) in tenderness development of loins from callipyge and normal genotype lambs. Loins ( M. longissimus lumborum ) from sixteen lambs across four genotypes were collected throughout 9 days of postmortem aging. The loins from callipyge lambs had more intact desmin and troponin T throughout aging periods, as well as less μ-calpain autolysis and more calpastatin compared to loins from other genotypes ( P < 0.05). Delayed onset of apoptosis was found in the callipyge loins indicated by less cytochrome c and more inactive procaspase-3 compared to normal lamb loins ( P < 0.05). Less degraded HSP27 was also consistently found in the callipyge loins compared with loins from normal lambs ( P < 0.001). The results found up-regulation of anti-apoptotic activities coincided with toughness in callipyge loins, which suggest apoptosis is likely involved in postmortem proteolysis and subsequent meat tenderization. Highlights: Relevance of heat shock proteins (HSP) in callipyge (CLPG) toughness was determined. CLPG loin had less myofibrillar proteolysis and greater toughness than normal loins. CLPG loin had less μ-calpain autolysis and more calpastatin than normal loins. Delayed onset of apoptosis was found in CLPG loins during aging. CLPG loins had less cytochrome c, caspase 3 and degraded HSP27 than normal loins.